Revising the Integration-Citizenship Nexus in Europe (IMISCOE Research Series, 2023)
This open access book critically re-examines the theoretical and empirical interconnections between integration and citizenship, specifically, naturalisation. With new, empirical-grounded analyses of what we term 'citizenship-integration nexus' the central, shared contribution is showcasing how membership is informally achieved through everyday integration —usually around, but sometimes in spite of, formal citizenship requirements. By providing evidence of a nexus disjuncture, the book contributes to critical dialogues on immigrant integration and political incorporation, relevant for policymakers, civil society actors, and academics alike.